Soft Tissue Cephalometric Norms for Bihar Ethnic Population - Rahul Munka; Vaibhav Shandilya; Harsh Kumar; Abhishek Sinha (International Healthcare Research Journal, 2019)
INTRODUCTION: A person's ability to recognize a beautiful face is innate, but translating this into defined treatment goals is problematic and various authors tried to relate the importance of soft-tissue esthetics with orthodontic diagnosis and treatment planning.AIM AND OBJECTIVES: To derive the Soft Tissue Cephalometric norms for the normal, well-balanced and esthetically pleasing faces of the Bihar ethnic population and to compare them with pre-established norms.MATERIALS AND METHOD: A sample of 60 subjects from an ethnic Bihar population residing in Patna, on the basis of facial symmetry, balance and pleasing appearance were observed from five sets of extra-oral photographs. Standardized lateral cephalometric radiographs were taken with metallic markers placed on various soft-tissue structures on the face using derma tapes. All lateral cephalometric films were traced and Soft Tissue Cephalometric Analysis was done.RESULTS: Total facial length was significantly less in males as compared to the Caucasians with 117.50±1.74 as mean value. Males had significantly less protrusive upper and lower lips in projection to TVL with a mean value of 0.77±0.77 and -3.13±0.73 respectively. Lower lip length in females was significantly decreased with a decreased lower third facial height with a mean value of 62.27±1.46. Total facial length was significantly less in females with a mean value of 115.40±1.99. Females had significantly more protrusive upper and lower lips in projection to TVL with a mean value of 1.90±0.84 and 1.93±0.74 respectively.CONCLUSION: The established norms in present study could be used as future reference for Orthodontic treatment in Bihar ethnic population.